Revolutionizing efficiency: The path to sustainable oilfield services in Indonesia's energy landscape – The case of Pertamina drilling services - Firmansyah Arifin; Sudarso Kaderi Wiryono; Sylviana Maya Damayanti; Gatot Yudoko (Heliyon)
Purpose: This study explores strategic and technological approaches for sustainable oil production in Indonesia, focusing on policy frameworks, eco-innovation, and supply chain resilience to align with national and global standards. It also analyzes the organizational transition of Pertamina Drilling Service Indonesia (PDSI) to better navigate industry challenges with the outcome of a framework sustainable practices. Design/methodology/approach: Utilizing Soft Systems Methodology (SSM) to analyze primary qualitative data, the research examines PDSI's adaptation to depict the current business environment and challenges both domestically and globally, addressing industry demands. It focuses on operational objectives, strategic asset management, regulatory compliance, and market positioning. SSM offers a comprehensive framework for understanding and modeling the organizational changes within PDSI. Findings: The transition to a functional organizational structure has led to enhanced operational efficiency, clearer role definition, and improved employee retention and development strategies at PDSI. The study also highlights the industry's challenges, including high risks, capital intensity, environmental concerns, and fluctuating oil prices, and how PDSI is strategically responding to these challenges. Research limitations/implications: The study faces limitations due to reliance on specific data sources and the inherent complexity of the oil and gas sector. However, it offers valuable insights into the dynamics of organizational change in a high-risk industry. Practical implications: The findings provide a roadmap for PDSI in addressing operational efficiency, human resource management, and organizational agility. This includes aligning business expansion with environmental sustainability and enhancing competitiveness through technological innovation. Social implications: By focusing on strategic employee development and retention, the study underscores the importance of human capital in the oil and gas industry, impacting social aspects of business operations. Originality/value: This research contributes to the understanding of organizational transitions in the oil and gas sector. It offers a unique perspective on how PDSI can achieve sustainable growth and industry leadership through a functional organizational structure, underlined by a comprehensive framework emphasizing efficiency, adaptability, and continuous improvement.